Uprawnienie do pochówku oraz pogrzeb płodu, noworodka, dziecka i osoby dorosłej w prawie polskim - Chciałowska, Anna (Kwartalnik Prawa Publicznego, 2016)
The main aim of this article is to present the states’ position regarding the matters connected with granting rights to the funeral. It also explains the process of the funeral of the fetus, infant, baptized and unbaptized child. In addition, it gives the list of people entitled to the funeral and the specified entity, which is responsible for the legal exercise of the right to the funeral. It also points the reader’s attention to the legal basis and conditions of the implementation of the funeral for adults and catechumens. The analysis of sources in Canon Law and Polish Law conducted in this thesis indicates that the issue of the right to the funeral, and its implementation is very complex, and therefore it requires research that also includes the above mentioned study. This thesis allows to understand the position of the state on burial law.